Transforming cities. Discourses of urban change. - (:unkn) unknown (Universitätsverlag Winter, 2018)
Today, the majority of people worldwide live in cities or metropolitan areas. This volume responds with a transdisciplinary approach to growing urbanisation and globalisation - climate change, energy change, secure jobs, affordable living, sustainable mobility, migration or demographic change. It brings together recent research in the areas of Urban and Media Studies, 19th- and 20th-century urban fiction and Victorian and neo-Victorian Studies. The contributors endeavor to compare various discourses of urban transformation - expansion, corruption, renewal, dereliction, adaptation - that have emerged in situations of rapid, uncontrolled change. Fields covered include the London Green Belt and ecocritical flânerie in New York, neo-Victorian streetwalking in novels by Peter Ackroyd and Michel Faber, the global impact of urban transformations on Dublin or Hong Kong, "slumming" in the TV series "Maison Close", "Ripper Street" and "Penny Dreadful" as well as Amsterdam's Red Light District and urban geographies of entertainment in London, from the Crystal Palace to the Millennium Dome.
Keywords: Stadtsoziologie; Stadtentwicklung; Stadtgeschichte; Großstadt; Bevölkerungsentwicklung; Sozialwandel; Strukturwandel; Verstädterung; Transformation; Globalisierung; Urbanisierung; Metropolregion; Millionenstadt; Stadttechnik; Bevölkerungswachstum; Slum; Stadtgrün; Kriminalität; Wahrnehmung; Medien